2010
DOI: 10.1177/0020715210368840
|View full text |Cite
|
Sign up to set email alerts
|

Conceptualizing ‘precarious prosperity’: Empirical and theoretical elements for debate

Abstract: Empirical studies have recently pointed towards a socio-structural category largely overlooked in social inequality research: the dynamic positions of households adjacent to those of the poor and yet not representing those of the established, more prosperous positions in society. These results suggest that the population in this category fluctuates into and out of poverty more often than moving into and out of secure prosperity. This category -still lacking theoretical conceptualization -is characterized by bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
35
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(40 citation statements)
references
References 26 publications
1
35
0
Order By: Relevance
“…This term refers to the socio-economic position of households that are situated just above the poverty threshold, but whose means to cope with life's contingences are few (Budowski et al 2010). Monica Budowski and her colleagues refined the term 'precarious prosperity' starting from Hübinger's(1996) empirical findings on a particular socio-structural category in Germany situ-ated above the poverty line but whose lived realities are similar to those in poverty.…”
Section: Comparative Research On Precarious Prosperitymentioning
confidence: 99%
See 4 more Smart Citations
“…This term refers to the socio-economic position of households that are situated just above the poverty threshold, but whose means to cope with life's contingences are few (Budowski et al 2010). Monica Budowski and her colleagues refined the term 'precarious prosperity' starting from Hübinger's(1996) empirical findings on a particular socio-structural category in Germany situ-ated above the poverty line but whose lived realities are similar to those in poverty.…”
Section: Comparative Research On Precarious Prosperitymentioning
confidence: 99%
“…Hübinger split the range of population's income in five equal parts both above and below the poverty line and found that in order to under-stand the challenges of upward and downward socio-economic mobility it is more meaningful to look at a zone of precariousness which extends beyond the poverty line and also encompasses the first three quintiles above this threshold. Building on this, Budowski et al(2010) claimed that such a struc-tural category could be identified in other socio-economic and cultural con-texts, and sought to design criteria to delineate it within international comparative research. An attempt to use this concept and its underlying research methodology in international settings concerned the comparative study of precarious prosperity in Chile, Costa Rica, Spain and Switzerland (Budowski et al 2010;Amacker et al 2013).…”
Section: Comparative Research On Precarious Prosperitymentioning
confidence: 99%
See 3 more Smart Citations